The sustainability of life. A vision from the feminist economy (Islas, 2021)
The fundamental principles of feminist economics are tackled from a new vision of development and sustainability, which has committed to life through a logic that differs from the classic economic criteria, far from economism and technocracy. The recognition of this vision leads us not to define the criteria of sustainability in a narrow way, but to observe them in close connection to the recognition and respect for diversity, a recognition that materializes in various ways by the use of resources and entails well-differentiated cultural and social trajectories with respect to each community. Although the need to achieve sustainable development is global, the proposals should not only target at the world economy, but also at regional and local economies and cultures. Therefore, there is a need to contextualize and implement solutions in development strategies that make less intensive use of natural resources.
Keywords: sustainability; development; feminist economics